Ameliorating effect of the biological Zinc nanoparticles in abamectin induced hepato-renal injury in a rat model: Implication of oxidative stress, biochemical markers and COX-2 signaling pathways - Aioub, Ahmed A. A.; Abdelnour, Sameh A.; Shukry, Mustafa; Saad, Ahmed M.; El-Saadony, Mohamed T.; Chen, Zhongli; Elsobki, Ahmed E. A. (Frontiers in Pharmacology, 2022)
Extensive use of abamectin (ABM) as an anthelmintic in veterinary systems adversely affects the health and welfare of animals and humans. Zinc nitrate nanoparticles (ZnNPs) have therapeutic benefits and ameliorate the effect of environmental pollutants. In this study, we assessed the ameliorative effect of ZnNPs against the sub-lethal toxicity of ABM in rats. Forty healthy rats were randomly separated into four groups (n=10); the control received normal saline and test rats were treated orally twice weekly with ABM (1 mg/kg bwt), ZnNPs (10 mg/kg bwt) and ABM+ ZnNPs for 28 days. Upon completion of the study period, blood and tissue samples were collected and prepared for hematological, biochemical, pathological, and immunohistochemical analysis. Our results showed that ABM treatment significantly decreased body weight gain (BWG), red blood cells (RBCs), hemoglobin (Hb), hematocrit (HC), and platelet (PLT); while it significantly increased white blood cells (WBCs) and lymphocytes. ABM also significantly decreased antioxidant enzyme activities (superoxide dismuthase (SOD), glutathione peroxidase (GPx), and catalase (CAT)) and increased hydrogen peroxide and malondialdehyde levels compared with other groups. ABM significantly raised alanine aminotransferase (ALT), aspartate amino transaminase (AST), and alkaline phosphatase (ALP) levels, which was restored by co-administration of ZnNPs. Moreover, ZnNPs ameliorated ABM-mediated negative histopathological changes in the liver and kidney tissues, exhibiting a significant protective effect. Cyclooxygenase 2 (COX-2)+ immuno-expression was reduced after pretreatment with ZnNPs. These findings suggested that co-administration of ZnNPs with ABM mitigated its toxicity by combating oxidative stress and boosting antioxidant capacity, indicating the efficacy of ZnNPs in attenuating ABM toxicity.